The relationship between functional potential and field performance in elite female wheelchair basketball players - Vanlandewijck, Y. C.; Evaggelinou, C.; Daly, D. J.; Verellen, J.; van Houtte, S.; Aspeslagh, V.; Hendrickx, R.; Piessens, T.; Zwakhoven, B. (Journal of Sports Sciences, 2004)
The functional classification system for wheelchair basketball is based on an analysis of the players' functional resources through field-testing and game observation. Under this system, players are assigned a score of 1 to 4.5. The aim of this study was to determine if the wheelchair basketball player classification system reflects the existing differences in performance of elite female players. During the World Championship for Wheelchair Basketball in Sydney 1998, eight teams were videotaped for three 40-min games for a total of 120 min per team. Fifty-nine female players (Class I [1 and 1.5 points] n = 12; Class II [2 and 2.5 points] n = 20; Class III [3 and 3.5 points] n = 13; Class IV [4 and 4.5 points] n = 14) were retained for a detailed performance analysis by means of the Comprehensive Basketball Grading System (CBGS). Two-way analysis of variance showed high point players to perform better compared with low point players for the majority of variables determining the quality of game performance. A lack of significant differences between two adjacent classes was explained on the basis of the methodological approach, the class-position relationship in this sample, and the performance level of women's wheelchair basketball. We conclude that the performance of elite female wheelchair basketball players is dependent on functional ability.